2021
DOI: 10.1542/peds.2020-030601
|View full text |Cite
|
Sign up to set email alerts
|

Current Prescription Opioid Misuse and Suicide Risk Behaviors Among High School Students

Abstract: BACKGROUND AND OBJECTIVES: In previous studies, researchers have reported that youth with a lifetime history of prescription opioid misuse (POM) are at an increased risk for suicidal ideation, planning, and attempts. In this study, we investigate whether the association between youth POM and suicide outcomes differs by recency of POM (ie, none, past, or current misuse). METHODS: In this report, we use data from the 2019 Youth Risk Behavior Survey to examine associations between recency of POM (current POM, pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Our study demonstrated lower odds of opioid use in association with suicidal behaviors. However, as per the study by Wilkins et al, any prescription opioid misuse (current and past misuse) is associated with increased students' risk of suicide-related behaviors but our study did not determine any causal association [25].…”
Section: Discussioncontrasting
confidence: 52%
“…Our study demonstrated lower odds of opioid use in association with suicidal behaviors. However, as per the study by Wilkins et al, any prescription opioid misuse (current and past misuse) is associated with increased students' risk of suicide-related behaviors but our study did not determine any causal association [25].…”
Section: Discussioncontrasting
confidence: 52%
“…Ultimately, 182 studies met the inclusion criteria; three studies only included event count and not participant sample size [13‐15]. A total of 53 (29%) studies employed cross‐sectional, population‐based and nationally representative observational designs [7,14,16–63]; 13 (7%) employed longitudinal, cohort‐based observational designs [64–76]; 4 (2%) employed case control designs [77–80]; 6 (3%) were randomised control trials [81–86]; 54 (30%) employed cross‐sectional data from convenience samples [72,87–139]; 10 (5%) employed longitudinal (including repeated cross‐sectional) data from nationally representative studies [15,17,140–146]; and 42 (23%) retrospectively assessed individual‐level data […”
Section: Resultsmentioning
confidence: 99%
“…Although observational studies have emphasized the association between substance use disorder (SUD) and suicide idea or behaviours, they were unable to establish causal relationships. 49, 50 Meanwhile, there are only a few related genetic association studies specifically focusing on correlated relationships between them. Instead, previous studies usually concentrated on SA with psychiatric disorders, especially MDD, 51 BD, 51, 52 and SCZ 53 ; or they just focused on mental disorders themselves.…”
Section: Discussionmentioning
confidence: 99%